Ostracod-based environmental reconstruction of Lake Koronia, (Central Greece) during the Holocene (2025)
Navrozidou, V., O. Koukousioura, S. Doani, P. Frenzel, M. Triantaphyllou, K. Albanakis, and G. Syrides. 2025. Ostracod-based environmental reconstruction of Lake Koronia, (Central Greece) during the Holocene. Presentation in 17th International Congress of the Geological Society of Greece. Lesvos island, Greece, 27-31 May 2025